Evaluasi Layanan Konseling Individual pada Kurikulum Merdeka terhadap Pengembangan Diri Siswa Menggunakan Model CIPP: Evaluation of Individual Counseling Services under the Kurikulum Merdeka (Independent Curriculum) regarding Student Self-Development Using the CIPP Model - Ella Nur Ramadhani; Nina Permata Sari; Muhammad Andri Setiawan (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Evaluation is a crucial component in various aspects of life, serving as an essential part of implementing activities and programs. Without evaluation, it is impossible to track a program's progress. This study aims to evaluate individual counselling services within the Kurikulum Merdeka (Independent Curriculum) framework regarding student self-development at SMA Negeri 12 Banjarmasin, utilising the CIPP (Context, Input, Process, Product) evaluation model. A qualitative approach was employed, with research subjects comprising the school principal, guidance and counselling teachers, and students. Data collection involved interviews, observation, and documentation, while data analysis encompassed data collection, data reduction, data display, and conclusion drawing/verification. The results indicate that, regarding the context aspect, the implementation of the Kurikulum Merdeka and individual counselling services effectively supports student self-development through active learning, potential development, and character strengthening. In terms of input, the services are supported by the competence of guidance and counselling teachers, student needs assessments, and adequate school facilities, although limitations remain regarding service media support. Regarding the process aspect, individual counselling services are conducted systematically, involving needs assessment, service delivery, the use of service media, and continuous follow-up. In terms of product, the individual counselling services have positively impacted student self-development across personal, social, academic, emotional, and career dimensions. Based on the evaluation using the CIPP model, the individual counselling service program at SMA Negeri 12 Banjarmasin has been implemented successfully and supports student self-development in personal, social, academic, emotional, and career aspects.